2021
DOI: 10.1039/d1cc03653j
|View full text |Cite
|
Sign up to set email alerts
|

2-Indolymethanols as 4-atom-synthons in oxa-Michael reaction cascade: access to tetracyclic indoles

Abstract: TThe first Brønsted acid-catalyzed oxa-Michael reaction cascade of 2-indolylmethanols with trione alkenes was accomplished. By using this practical approach, a variety of tetracyclic indoles were readily created in ordered sequence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Based on the current experimental results and previous reports, 5 a ,7 plausible reaction pathways were suggested (Scheme 5). The enolization of azlactone 2a afforded its active form.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Based on the current experimental results and previous reports, 5 a ,7 plausible reaction pathways were suggested (Scheme 5). The enolization of azlactone 2a afforded its active form.…”
mentioning
confidence: 52%
“…6 Recently, we accomplished the Brønsted acid-catalyzed oxa-Michael reaction cascade of triketone enones with 2-indolylmethanols for the construction of tetracyclic indoles, and found that the chemoselectivity could be reversed by employing different Brønsted acids. 7 Along this line, we questioned whether the regio-reversed domino process of triketone enones would be feasible and if the stereoselectivity could be simultaneously controlled. Herein, we report the reaction cascade of triketone enones with azlactones (Scheme 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The electron density plays an important role in intramolecular Friedel–Crafts cyclization step and the electron‐donating group has the ability to increase the electron density of the indole ring, which enhances the rate of the intramolecular cyclization. The relative stereochemistry of the newly generated stereocenters was assigned by comparison of the NMR with that reported in the literature [5j] …”
Section: Resultsmentioning
confidence: 99%
“…In 2021 Mie et al . constructed [5j] dihyropyranoindoles from 2‐indolylmethanol and trione alkene in presence of strong Brønsted acid (PhO) 2 OPOH. However, they metioned that only strong acid e. g. (PhO) 2 OPOH, TFA, TsOH, MsOH etc.…”
Section: Introductionmentioning
confidence: 99%